2020
DOI: 10.55713/jmmm.v30i2.708
|View full text |Cite
|
Sign up to set email alerts
|

Green-based corrosion protection for mild steel in 3.5 % NaCl and distilled water medias: Jatropha curcas and Roselle extracts

Abstract: In this study, the natural sources of Jatropha curcas and Hibiscus Sabdariffa calynx (Roselle) extracts as green corrosion inhibitors were employed to improve the corrosion resistance of mild steel in simulated (3.5% NaCl) and distilled water medias. The inhibiting performance of two types of extracts was studied by visual inspection, microscope analysis, and various electrochemical measurements and the data of corrosion rate were statistically analyzed. The main phenolic compounds of Jatropha and Roselle extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Its leaves and seeds are rich in secondary metabolites and have been investigated for their corrosion inhibitory properties. Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Its leaves and seeds are rich in secondary metabolites and have been investigated for their corrosion inhibitory properties. Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%